2014
DOI: 10.1163/15685276-12341344
|View full text |Cite
|
Sign up to set email alerts
|

The Youth-Crisis Model of Conversion: An Idea Whose Time Has Passed?

Abstract: Initially formulated in the 1970s when large numbers of former counterculturists were joining alternative religions, the youth-crisis model of conversion posited that new recruits were predominantly young people whose involvement could be explained as a function of their youth (e.g., as an adolescent developmental crisis). The present study presents statistics on recruits to seven different contemporary new religions that fun damentally challenge this item of conventional wisdom. Six out of seven data sets als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Along with the convention that NRM members are more highly educated, these older studies have continued to inform the view that recruits are generally younger, that NRMs are dominated by one or the other sex, that their members primarily became involved through preexisting social networks, and that they tended to have fewer or weaker ideological alignments prior to joining. However, a number of recent, diachronically informed studies (e.g., Lewis , ; Lewis and Baumann ) have decisively demonstrated that the NRM field has been relying on outdated demographic data to inform our understandings of the traits of NRM members. With few exceptions, such as Rochford's () monograph on the Hare Krishna movement, researchers have, in effect, been studying NRMs as if they were static entities, failing to capture the change in membership demographics over time.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the convention that NRM members are more highly educated, these older studies have continued to inform the view that recruits are generally younger, that NRMs are dominated by one or the other sex, that their members primarily became involved through preexisting social networks, and that they tended to have fewer or weaker ideological alignments prior to joining. However, a number of recent, diachronically informed studies (e.g., Lewis , ; Lewis and Baumann ) have decisively demonstrated that the NRM field has been relying on outdated demographic data to inform our understandings of the traits of NRM members. With few exceptions, such as Rochford's () monograph on the Hare Krishna movement, researchers have, in effect, been studying NRMs as if they were static entities, failing to capture the change in membership demographics over time.…”
Section: Introductionmentioning
confidence: 99%